2013
DOI: 10.1007/s11665-013-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Study of the Effect of Prior Axial Compression/Torsion on the Axial-Tensile Strength of PPTA Fibers

Abstract: A comprehensive all-atom molecular-level computational investigation is carried out in order to identify and quantify: (i) the effect of prior longitudinal-compressive or axial-torsional loading on the longitudinaltensile behavior of p-phenylene terephthalamide (PPTA) fibrils/fibers; and (ii) the role various microstructural/topological defects play in affecting this behavior. Experimental and computational results available in the relevant open literature were utilized to construct various defects within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Grujicic et al 56,[62][63][64][65] reported that defect's type, size and concentration are sensitive functions of the PPTA fiber fabrication (polymer synthesis, dope preparation and spinning process) -which are summarized in the present review in section 2.…”
Section: Structural Defectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Grujicic et al 56,[62][63][64][65] reported that defect's type, size and concentration are sensitive functions of the PPTA fiber fabrication (polymer synthesis, dope preparation and spinning process) -which are summarized in the present review in section 2.…”
Section: Structural Defectsmentioning
confidence: 95%
“…An outstanding analysis of PPTA fibers at multi scale levels is investigated by Grujicic et al 56,[62][63][64][65] . The computational investigations properly described the material models which are used to achieve the material (PPTA) behaviour at the length-scale levels from chemical structure (atoms) to composite structure (laminate) with brief description in eight levels.…”
Section: Ppta Computational Modellingmentioning
confidence: 99%
“…The effect of AC and TC deformation modes on the fiber tensile failure strength has not been studied extensively. There are few atomistic simulations studies [20][21][22][23][24][25] that focused on the elastic and strength properties of Kevlar ® and PE crystal. Rutledge et al [20] have determined the elastic properties of Kevlar ® crystal through atomistic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Rutledge et al [20] have determined the elastic properties of Kevlar ® crystal through atomistic simulations. Grujicic et al [21,22] studied the properties of Kevlar ® filament using non-reactive force field COMPASS (Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies) [26]. In one study [21], they investigated the effects of microstructural and topological defects such as chain ends, inorganic-solvent impurities, chain misalignments, and sheet stacking faults on the strength, ductility, and stiffness of PPTA filament.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting defects can also degrade mechanical properties of the PPTAbased materials, and their effect has to be accounted for in the analysis of the ballisticprotection resistance of the PPTA-based materials. To address this problem, a series of allatom and coarse-grained molecular-level computational analyses is carried out in the present work [11][12][13]. Specifically, the effect of the preludial handling-induced deformation modes such as fiber/yarn transverse compression due to inter-yarn contacts, fiber/yarn twist/axialcompression, and fiber/yarn bending (encountered primarily in warp yarns) and the associated formation of kink-bands has been investigated.…”
Section: Effect Of Fiber-/yarn-handling-induced Defects On Ppta-fibermentioning
confidence: 99%